March 23, 2017

Post a New Question

Posted by on Friday, May 27, 2011 at 10:14pm.

sec(90degrees -theta)

  • trig - , Friday, May 27, 2011 at 10:28pm

    sec(90 -theta) = 1/cos(90 - theta)
    = 1/(cos90 cos theta + sin 90 sin theta)
    = 1/sin theta
    = csc theta

    You could get the same result by considering a right triangle. The sec of one acute angle is the csc of the other.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question